An estimation of the effect of a possible wind speed increase on the ocean mixed layer depth at the northern Patagonian continental shelf - Alvarez, Ezequiel (2015)
A possible deepening of the ocean mixed layer is investigated at two selected points of the Patagonian continental shelf where a significant positive wind speed trend is estimated. Using a 1-dimensional vertical numerical model on a long term simulation (1979-2011) it is found that the mixed layer thickness presents a significant and positive trend of about 10±1.5 cm/yr. The model is forced by atmospheric data from NCEP/NCAR 1 reanalysis and tidal constituents from TPXO 7.2 global model. Several numerical experiments are carried out in order to evaluate the impact of the different atmospheric variables considered in this study (wind components, air temperature, atmospheric pressure, specific humidity and cloud coverage). As a result it is found that a possible increase in the wind speed should be considered as a very significant factor for deepening the ocean mixed layer at the northern Patagonian continental shelf.